1992
DOI: 10.1007/bf02540952
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of oil extraction from corn germ

Abstract: This paper describes the effect of temperature and moisture content on the kinetics of oil extraction from corn germ flakes prepared by a dry degermination process. The experiments were carried out according to the factorial design 3 ~. The moisture content in the extracted material was varied in the range 8%-12%, whereas the extraction temperature varied in the range 52.5°C-57.5°C. From the method of response surfaces, a functional dependence was established between the extraction rate, the moisture content i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In this work, the rigorous equilibrium stage model (RADFRAC) is employed to simulate all involved columns including DC, EDC, and SRC for achieving accurate simulation results. In addition, the SRK and UNIFAC [59] models are, respectively, employed to perform the thermodynamic calculations for the EB distillation process simulation [60].…”
Section: Process Simulationmentioning
confidence: 99%
“…In this work, the rigorous equilibrium stage model (RADFRAC) is employed to simulate all involved columns including DC, EDC, and SRC for achieving accurate simulation results. In addition, the SRK and UNIFAC [59] models are, respectively, employed to perform the thermodynamic calculations for the EB distillation process simulation [60].…”
Section: Process Simulationmentioning
confidence: 99%
“…In the industrial production and utilization of corn germ, the moisture content of corn germ is usually determined according to the requirement of processing technology. Therefore, the moisture content of corn germ is various aiming for different applications, which could range from 3 to 13% [19][20][21][22].…”
Section: Quality Changes Of Maize Germ During Storagementioning
confidence: 99%
“…However, a temperature higher than 80 C can cause solubilization of organic matter into the solvent (hindering the oil measurement), and it may also decrease transesterification efficiency. Karlovic et al (1992) investigated the effect of temperature on the kinetics of oil extraction from corn germ and reported that increasing the temperature enhances the capacity of solvents to dissolve the oil because of the thermal energy that overcomes the cohesive and adhesive interactions. Furthermore, the collision theory states that two molecules will only react if they have enough activation energy (Diphare & Muzenda, 2013).…”
Section: Effect Of Temperaturementioning
confidence: 99%